Crosstalk between the equilibrative nucleoside transporter ENT2 and alveolar Adora2b adenosine receptors dampens acute lung injury. Issue 8 (19th April 2013) - Eckle, Tobias; Hughes, Kelly; Ehrentraut, Heidi; Brodsky, Kelley S.; Rosenberger, Peter; Choi, Doo‐Sup; Ravid, Katya; Weng, Tingting; Xia, Yang; Blackburn, Michael R.; Eltzschig, Holger K.
Abstract : The signaling molecule adenosine has been implicated in attenuating acute lung injury (ALI). Adenosine signaling is terminated by its uptake through equilibrative nucleoside transporters (ENTs). We hypothesized that ENT‐dependent adenosine uptake could be targeted to enhance adenosine‐mediated lung protection. To address this hypothesis, we exposed mice to high‐pressure mechanical ventilation to induce ALI. Initial studies demonstrated time‐dependent repression of ENT1 and ENT2 transcript and protein levels during ALI. To examine the contention that ENT repression represents an endogenous adaptive response, we performed functional studies with the ENT inhibitor dipyridamole. Dipyridamole treatment (1 mg/kg; EC50 =10 μM) was associated with significant increases in ALI survival time (277 vs. 395 min; P <0.05). Subsequent studies in gene‐targeted mice for Ent1 or Ent2 revealed a selective phenotype in Ent2 ‐/‐ mice, including attenuated pulmonary edema and improved gas exchange during ALI in conjunction with elevated adenosine levels in the bronchoalveolar fluid. Furthermore, studies in genetic models for adenosine receptors implicated the A2B adenosine receptor (Adora2b) in mediating ENT‐dependent lung protection. Notably, dipyridamole‐dependent attenuation of lung inflammation was abolished in mice with alveolar epithelial Adora2b gene deletion. Our newly identified crosstalk pathway between ENT2 and alveolar epithelial Adora2b in lung protection during ALI opens possibilities for combined therapies targeted to this protein set.—Eckle, T., Hughes, K., Ehrentraut, H., Brodsky, K. S., Rosenberger, P., Choi, D.‐S., Ravid, K., Weng, T., Xia, Y., Blackburn, M. R.Eltzschig, H. K., Crosstalk between the equilibrative nucleoside transporter ENT2 and alveolar Adora2b adenosine receptors dampens acute lung injury. FASEB J. 27, 3078–3089 (2013). www.fasebj.org